EXPERIENCE REPORT OF THE EXTENSION PROGRAM MADE BY APRENDA A SALVAR UMA VIDA IN SENADOR CANEDO (CIPEEX, 2022)
THE HIGH PERCENTAGE OF DEATHS CAUSED BY CARDIAC ARREST AND THE INCAPACITY OF THE LAY POPULATION TO DEAL WITH THESE CASES IS ASTONISHING. THEREFORE, A PROGRAM WAS EXECUTED IN A SMALL TOWN, CALLED SENADOR CANEDO, WITH THE OBJECTIVE TO ENABLE THE LOCAL CITIZENS SO THEY CAN MANAGE CARDIOPULMONARY RESUSCITATION (CPR), ONLY USING THEIR HANDS, AS WELL AS THE CHOKING MANEUVER ALSO KNOWN AS HEIMLICH MANEUVER. THUS, WE SEARCH TO REPORT ONE OF THE ACTIVITIES MADE IN A TOWN, CALLED SENADOR CANEDO, BY THE PROJECT APRENDA A SALVAR UMA VIDA (ASV), THAT HAS THE PURPOSE TO SPREAD THE KNOWLEDGE OF CPR. IN THAT CONTEXT, 15 MONITORS WERE SELECTED, WITH THE BASIC LIFE SUPPORT OF THE ASV, SO THEY CAN TEACH THE POPULATION THROUGH SIMULATION DUMMIES CERTIFIED BY THE AMERICAN HEART ASSOCIATION (AHA). HENCE, THE PROJECT WAS ACCOMPLISHED WITH 150 PEOPLE, WHICH WERE DIVIDED IN 3 STATIONS, COMPOSED OF: ADULT CPR, HEIMLICH IN BABIES AND HEIMLICH IN ADULTS. IN THIS WAY, IT WAS NOTICED IN THE EXPERIENCE, A HIGH INTEREST AND THE ABILITY TO PERFORM THE MANEUVERS TAUGHT BY THE PARTICIPANTS, WHO EVALUATED THE ORGANIZATION OF THE WORKSHOP AND ALSO THEIR KNOWLEDGE ABOUT THE SUBJEIN A QUESTIONNAIRE. THEREFORE, THE OBJECTIVE OF THIS STUDY IS TO REPORT ONE OF THE ACTIONS CARRIED OUT IN THE CITY OF SENADOR CANEDO BY THE UNIEVANGELICA MEDICAL COURSE EXTENSION PROGRAM - APRENDA A SALVAR UMA VIDA - WHICH AIMS TO FULFILL THIS OBLIGATION TO THE LAY POPULATION, AND DISSEMINATE THE KNOWLEDGE ABOUT CPR AND HEIMLICH.KEY-WORDS: CARDIOPULMONARY RESUSCITATION, HEART ATTACK, ACADEMIC TRAINING
Keywords: cardiopulmonary resuscitation; heart attack; Academic training